(untitled) (Innovation & Development in Engineering and Applied Science, 2021)
One of the methods used to control pain, when a patient has had a fracture at the level of the femur diaphysis, is skeletal traction [1]. The following highlights advances in the design of a traction ferrule for preoperative stabilization in femur fractures. For this purpose, a solution was proposed, dimensioned according to the anthropometric characteristics of adult patients. A material for hospital use was selected. The stress analysis was carried out on the basis of the simulation of two positions, in which the splint will operate during its use. A program based on the finite element method was used for numerical calculation. Results were obtained to ensure the safety of the device, and the criteria established within the design framework, such as the stability of the device, ergonomics and the possibility of placing the ferrule in different positions, were verified.